1994
DOI: 10.1182/blood.v83.2.415.415
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric assessment of human MIC2 expression in bone marrow, thymus, and peripheral blood

Abstract: The cell-surface expression of the MIC2 antigen defined by the monoclonal antibody 12E7 was investigated on human leukocytes in bone marrow (BM), thymus, and peripheral blood (PB) using multiparameter flow cytometry and cell sorting. In contrast to preceding reports, we found that the MIC2 antigen is not restricted to T cells and monocytes. We show that it is also expressed in the B cell and in the granulocytic lineage, the levels of expression being related to distinct maturational stages. CD34+ cells of BM w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(48 citation statements)
references
References 33 publications
1
42
0
1
Order By: Relevance
“…Furthermore, CD99 expression was observed in normal tissues. 34 Presently, CD99 is best established as a diagnostic marker for Ewing sarcoma and primitive neuroectodermal tumours, 35 although CD99 immunoreactivity has also been shown in several other malignancies, e.g., hematopoietic neoplasm, 36 synovial sarcoma, 37 solitary fibrous tumours, 38 testicular and ovarian sex cord tumours 39,40 and breast cancer. 41 In association studies, loss of CD99 was found to be associated to poor prognosis in patients with osteosarcoma, 13 pancreatic endocrine tumours 42 and gastric adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CD99 expression was observed in normal tissues. 34 Presently, CD99 is best established as a diagnostic marker for Ewing sarcoma and primitive neuroectodermal tumours, 35 although CD99 immunoreactivity has also been shown in several other malignancies, e.g., hematopoietic neoplasm, 36 synovial sarcoma, 37 solitary fibrous tumours, 38 testicular and ovarian sex cord tumours 39,40 and breast cancer. 41 In association studies, loss of CD99 was found to be associated to poor prognosis in patients with osteosarcoma, 13 pancreatic endocrine tumours 42 and gastric adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…CD99 is expressed in 80-90% of T-LBLs [32], and appears to correlate with TdT expression [33]. In the thymus, CD99 is expressed at high levels not only in very early T-lineage cells but also in CD4+CD8+ or double-positive (DP) thymocytes [34]. The function of this protein at the early DN stage of development is not known, but a role in the mediation of apoptosis of maturing (DP) thymocytes was demonstrated [35].…”
Section: Discussionmentioning
confidence: 99%
“…CD34 does not specifically identify HPC subpopulations responsible for short-and long-term engraftment (8,31). With respect to short-term engraftment, which is the major goal in the supportive use of HPCs, the transplanted numbers of CD34 ϩ ,33 Ϫ cells have been reported to correlate significantly better with the rates of neutrophil reconstitution than those of the entire CD34 ϩ population (27).…”
Section: Questions To Be Addressedmentioning
confidence: 99%